Characterization of Eurycoma longifolia (Tongkat Ali) Essential Oils Extracted by Microwave Assisted Extraction - Ghazi Faisal, Najmuldeen; Hariitaraan, Fatmanathan; Ghasak, Ghazi Faisal; Zulkafli, Hassan (Open Science Publishers LLP Inc., 2017)
The main objective of this research is to extract and characterize the essential oils of Eurycoma longifolia jack (Tongkat Ali) root using microwave assisted extraction (MAE) The effect of various process parameters such as extraction time (5 min, 10 min, 15 min, 20 min, 30min, and 45 min), microwave power (200W, 225W, 250W, 275W, 300W and 400W) and raw material to solvent ratio (RMTSR) (1:6, 1:8, 1:10 and 1:12) on the yield and its major constituents were investigated in this study to obtain the optimum conditions for the extraction process. The pure essential oil obtained was characterized using gas chromatography mass spectroscopy (GCMS) techniques. The findings showed that the optimal conditions for the microwave assisted extraction of Eurycoma longifolia are 10 minutes extraction time, 225W microwave power and 1:10 for (RMTSR) with the maximum yield percentage of 1.91% .